The Concept and Lived Experience of the Notion of 'Cool' for Myself and for Young Adolescents: In-between Life-writing and Interpretive Study - Head, Robert (Université d'Ottawa / University of Ottawa, 2015)
Autobiographical life-writing as literary métissage about cool through stories grounded in auto-ethnographic reflection as a|r|t|ographer. An act of literary sharing. A past to present summed up as parts, as portraits or vignettes, building towards an attempted understanding of cool. Introspective reflection on cool supported by photographs, drawing, paintings, and poetry. A consideration of Franco Ontarian minority language secondary school population adolescent conceptions and notions of cool (Drolet et al, 2009). An inquiry into cool presented as a bioecological album (Urie Bronfenbrenner, 1979, 1994). A life-long journey from developing childhood cool to middle school cachet cool to high school contrarian cool to old school cool. Childhood to contrarian to cachet to Bieber’d [fucked] to adult cool. Historical cool. What is cool?
Keywords: Cool; a|r|t|ography; Bronfenbrenner; Drolet; adolescent; developmental; bio-ecological; life-writing; contrarian-cool; cachet-cool; Bieber'd-cool